Detection and genetic analysis of group II capsules in aeromonas hydrophila - Zhang, Y.L.; Lau, Y.L.; Arakawa, E.; Leung, K.Y. (2003)
The genetic organization and sequences of the group II capsule gene cluster of Aeromonas hydrophila PPD134/91 have been determined previously. The purified capsular polysaccharides can increase the ability of avirulent strain PPD35/85 to survive in naive tilapia serum but have no inhibitory effect on the adhesion of PPD134/91 to carp epithelial cells. In this study, the presence of group II capsules among 33 randomly chosen A. hydrophila strains was examined by electron microscopy and genetic analysis. Ten strains were found to produce group II capsules. A PCR detection system was developed to identify two types of group II capsules (IIA and IIB) based on their genetic organization in the region II gene clusters. Group IIA capsules in the authors' collection of A. hydrophila strains are mainly found in the O:18 and O:34 serogroups, while group IIB capsules are found in the O:21 and O:27 serogroups. The presence of group II capsules in A. hydrophila strongly correlates with the serum and phagocyte survival abilities (seven out of ten strains). The results indicate that the authors' PCR detection system can constitute a reliable assay for the classification of group II capsules in A. hydrophila.